Three-dimensional co-culture of FRET based cancer cells and fibroblasts for modeling in vivo tumor - Kashmeena Parwyn Muruges (2015)
Three-dimensional (3D) in vitro cultures are known to recapitulate the physiological microenvironment present in in vivo tumors. The 3D spheroid model is an established model used in cancer research. However, the use of end-point assays in these studies do not allow for real-time analysis of tumorigenesis and drug response. Here, the use of FRET-based cancer cells allowed for real-time imaging in the study of cancer development and anticancer drug evaluation. First, the influence of two-dimensional (2D) and 3D culture on breast cancer cells (231-C3 and MCF7-C3) was examined. This was done by analysing the morphological differences, as well as cell growth. The 3D spheroid model was then implemented in further investigations as it was found to recapitulate the tumor microenvironment more accurately. Taking into account the complex cellular interactions in tumors in vivo, a co-culture system of tumors cells with stromal fibroblasts of varying concentrations was set up in order to identify the best model that mimics physiological conditions. The use of fluorescence imaging enabled the visualization of the breast cancer cells within the three-dimensional spheroids. Finally, two anti-cancer drugs, doxorubicin and paclitaxel were tested on the spheroid model to study the effects that each exerts on the 3D spheroids. This work underscores the importance of a 3D microenvironment in the progression of tumor development. The 3D co-culture model can serve as a useful tool when it is extrapolated to drug studies in order to evaluate the clinical effectiveness of therapeutic drugs on cancerous cells.